ANALISIS KESULITAN GURU DALAM MERANCANG MEDIA PEMBELAJARAN DIGITAL PADA MATA PELAJARAN IPS MI/SD - Enmilda Putri, Rara; Latmini Lasari, Yufi (Program Studi Pendidikan Guru Madrasah Ibtidaiyah, 2024)
The purpose of this research is to provide a description of the difficulties faced by teachers in designing digital learning media. This study employs a qualitative method with a descriptive approach. The subjects in this research are fourth-grade homeroom teachers at SD N 06 Batipuh Selatan, with data collection techniques including observation, interviews, and documentation. The research instrument used consists of questions directed to the research informants, with five questions that have been answered. The research findings indicate that teachers still struggle to create digital learning media effectively